2016
DOI: 10.1038/ijo.2016.198
|View full text |Cite
|
Sign up to set email alerts
|

Association of childcare arrangement with overweight and obesity in preschool-aged children: a narrative review of literature

Abstract: The time children spend in childcare overlaps with daily meals and opportunities to be active. Thus these environments have the opportunity to promote-or hinder-healthy weight gain among children who attend them. The purpose of this narrative review was to compile findings from studies examining childcare type and weight outcomes among preschool-age children. A literature search was conducted using PubMed, PsychInfo and ERIC. Inclusion criteria were infant- to 5-year-old children exposed to any type of childca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…provided by nurseries, playgroups, nannies/au pairs, preschools and childminders), particularly when the care was provided by grandparents (three studies in the review reported an association). Similar inconsistent findings were reported in a recent narrative review of 18 studies examining the same topic, although in this review the authors found that the majority of studies reported no association between childcare type and risk of childhood overweight and obesity (Swyden et al 2016).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…provided by nurseries, playgroups, nannies/au pairs, preschools and childminders), particularly when the care was provided by grandparents (three studies in the review reported an association). Similar inconsistent findings were reported in a recent narrative review of 18 studies examining the same topic, although in this review the authors found that the majority of studies reported no association between childcare type and risk of childhood overweight and obesity (Swyden et al 2016).…”
supporting
confidence: 77%
“…Similar inconsistent findings were reported in a recent narrative review of 18 studies examining the same topic, although in this review the authors found that the majority of studies reported no association between childcare type and risk of childhood overweight and obesity (Swyden et al . ).…”
Section: Weight Gain During the Preschool Years And Childcare Exposurementioning
confidence: 97%
“…In particular, grandparents are an important source of child care worldwide, providing care to approximately one-quarter of children in the US 19 , UK 20 , and Australia 21 , with the prevalence highest among children under 5 years. Although child care type may not be associated with child weight status per se 22 , the nutrition and physical activity environments within these settings can impact on children's health outcomes. Grandparents could therefore play a potential role in the prevention of obesity-related diet and activity behaviours in young children.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, those authors suggest CBC may protect against overweight by promoting a healthier diet and providing health care [62]. Yet other studies have found no association between CBC and childhood overweight [67][68][69][70][71][72][73][74]. Attending CBC could be associated with lower risk of child overweight or obesity through several pathways, including planned nutritional programs and learning environments, healthy eating, regular opportunities for physical activity, regular bedtime and rise time, and reduced screen time (eg, computers, mobile phones, television) [62,63,75,76].…”
Section: Viewpoints Papersmentioning
confidence: 98%